CuCr NLDH-Graphene oxide blended polyvinyl chloride ultrafiltration membrane with improved permeability and antifouling behavior - Mehrabani, Seyed Ali Naziri; Rad, Tannaz Sadeghi; Vatanpour, Vahid; Khataee, Alireza; Kaya, Mustafa; Zeytuncu, Bihter; Koyuncu, Ismail (Elsevier, 2023)
The modification of filtration membranes with the aim of improving their permeability, stability, and antifouling properties is essential, which can be achieved by the development of novel materials or methods. In this context, the utilization of new nanomaterials is one of the considered approaches for polymeric membrane modification. In this study, the applicability of CuCr NLDH-GO incorporation with the objective of improving hydrophilicity, permeability, and antifouling properties of polyvinyl chloride (PVC) ultrafiltration membrane is reported. After synthesis of CuCr NLDH-GO by co-precipitation method, its effect on the performance of PVC membrane was investigated by incorporation of different concentrations (0-2 wt%) of CuCr NLDH-GO. The significant decline of the water contact angle from 76.4 degrees to 63.5 degrees indicated the hydrophilicity improvement. This hydrophilic property was effective for almost twofold enhancement of the pure water permeability from 23.7 L/m2.h.bar of the bare membrane to 53.7 L/m2.h.bar of the membrane containing 1 wt% CuCr NLDH-GO. Moreover, the modified membranes indicated improved antifouling performance by increasing flux recovery ratio values from 54.3 % to 65 %. The performance of membranes in rejection of two different dyes, including reactive yellow 160 (RY160) and reactive black 5 (RB5) showed that the incorporation of CuCr NLDH-GO is not only effective for antifouling behavior but also suitable for improving dye rejection of membranes.
Keywords: Ultrafiltration; Polyvinyl chloride; Antifouling; Dye rejection; CuCr NLDH-GO